Smectite deposits in Marathon Valley, Endeavour Crater, Mars, identified using CRISM hyperspectral reflectance data - V. K. Fox; R. E. Arvidson; E. A. Guinness; S. M. McLennan; J. G. Catalano; S. L. Murchie; K. E. Powell (Geophysical Research Letters)
Abstract The ~100 m wide Marathon Valley crosscuts the Cape Tribulation rim segment of the 22 km diameter, Noachian‐age Endeavour impact crater on Mars. Single‐scattering albedo spectra retrieved from three Compact Reconnaissance Imaging Spectrometer for Mars (CRISM) Full‐Resolution Targeted (FRT, regularized to 18 m/pixel) and two Along Track Oversampled (ATO, regularized to 12 m/pixel) observations indicate the presence of Fe3+‐Mg2+ smectite exposures located in Marathon Valley with combination vibration metal‐OH absorption strength comparable to smectite spectral signatures in Mawrth Vallis. The Opportunity rover was directed to the exposures and documented the presence of Shoemaker formation impact breccias that have been isochemically altered, likely by fracture‐controlled aqueous fluids.